2018
DOI: 10.1140/epje/i2018-11650-7
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the electroosmotic flow of a two-layer electrolyte-dielectric system with external pressure gradient⋆

Abstract: The stability of the electroosmotic flow of electrolyte-dielectric viscous liquids under the influence of the DC and AC electric fields along with the external pressure gradient is studied theoretically. Liquids are bounded by two infinite parallel plates. The lower wall bordering the electrolyte is assumed to be a charged surface, and the upper wall is electrically isolated. The charge at the lower boundary is assumed to be immobile, while the surface charge at the free surface is assumed to be mobile. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Several modes of the body behavior depending on the rate of the cavity rotation, i.e., the ratio of the centrifugal force of inertia and the gravity, are detected. 10) Stability of the electro-osmotic flow of electrolyte-dielectric viscous liquids under the influence of the DC and AC electric fields along with the external pressure gradient is studied in [10]. It is found that in the DC case, the external pressure could either stabilize or destabilize the flow depending on the relative directions of the electro-osmotic flow and the pressure-driven flow.…”
Section: )mentioning
confidence: 99%
“…Several modes of the body behavior depending on the rate of the cavity rotation, i.e., the ratio of the centrifugal force of inertia and the gravity, are detected. 10) Stability of the electro-osmotic flow of electrolyte-dielectric viscous liquids under the influence of the DC and AC electric fields along with the external pressure gradient is studied in [10]. It is found that in the DC case, the external pressure could either stabilize or destabilize the flow depending on the relative directions of the electro-osmotic flow and the pressure-driven flow.…”
Section: )mentioning
confidence: 99%
“…The commonly used microfluidic non-mechanical actuation methods mainly include electroosmotic [15,16,17], magnetic [18,19], optical [20,21,22], thermal [23,24], and piezoelectric [25,26,27]. As a common microfluidic driving method, piezoelectric actuation has been widely used due to its low cost, easy operation, and high efficiency [28,29].…”
Section: Introductionmentioning
confidence: 99%